Genomic analysis of Agrobacterium radiobacter DSM 30147T and emended description of A. radiobacter (Beijerinck and van Delden 1902) Conn 1942 (Approved Lists 1980) emend. Sawada et al. 1993. Issue 3 (November 2014) - Zhang, Linshuang; Li, Xiangyang; Zhang, Feng; Wang, Gejiao
Abstract Agrobacterium radiobacter is the only known non-phytopathogenic species inAgrobacterium genus. In this study, the whole-genome sequence ofA. radiobacter type strain DSM 30147T was described and compared to the other availableAgrobacterium genomes. This bacterium has a genome size of 7, 122, 065 bp distributed in 612 contigs, including 6, 834 protein-coding genes and 41 RNA genes. It harbors a circular chromosome and a linear chromosome but not a tumor-inducing (Ti) plasmid. To the best of our knowledge, this is the first report of a genome from theA. radiobacter species. In addition, an emended description ofA. radiobacter is described. This study reveals information that enhances the current understanding of its non-phytopathogenicity and its phylogenetic position withinAgrobacterium genus.